2015
DOI: 10.1038/micronano.2015.39
|View full text |Cite
|
Sign up to set email alerts
|

Chip-scale gas chromatography: From injection through detection

Abstract: Miniaturized gas chromatography (µGC) systems hold potential for the rapid analysis of volatile organic compounds (VOCs) in an extremely compact and low-power enabled platform. Here, we utilize microfabrication technology to demonstrate the single chip integration of the key components of a µGC system in a two-step planar fabrication process. The 1.5 Â 3 cm microfluidic platform includes a sample injection unit, a micromachined semi-packed separation column (µSC) and a micro-helium discharge photoionization de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 31 publications
0
45
1
2
Order By: Relevance
“…Reconciling the trade offs among VOC mixture pre-selection, pre-concentration, separation, and recognition/detection functions was central to realizing effective system-level performance. Collectively, the operational features and performance characteristics of the PEMM-1 prototype demonstrated in this study exceed those demonstrated with other prototype μGCs reported to date 28,29,[31][32][33][34][35][36][50][51][52][53] . Future work on optimizing sensor coating strategies should yield improvements in peak shapes and reductions in LODs.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…Reconciling the trade offs among VOC mixture pre-selection, pre-concentration, separation, and recognition/detection functions was central to realizing effective system-level performance. Collectively, the operational features and performance characteristics of the PEMM-1 prototype demonstrated in this study exceed those demonstrated with other prototype μGCs reported to date 28,29,[31][32][33][34][35][36][50][51][52][53] . Future work on optimizing sensor coating strategies should yield improvements in peak shapes and reductions in LODs.…”
Section: Discussioncontrasting
confidence: 42%
“…Notwithstanding the OPH sensor, the excessive tailing of which renders it of less value as a detector, the speed and resolution obtained were quite good. Taken together with the peak capacities, which ranged from 80 to 103 among the sensors for a 4 min separation based on MBK, and the peak production rates, which ranged from 20-25 per min (also based on MBK), the chromatographic performance of the PEMM-1 exceeds that of other reported GC prototypes employing microfabricated separation components 28,29,[31][32][33][34][35][36][50][51][52][53] .…”
Section: Pemm-1 24 Voc Analysis With Vapor Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has been miniaturized with the goal to achieve sensor systems for nearly continuous monitoring operating in adsorption/desorption cycles. However, these systems today are typically based on closed pre-concentrators combined with micro-pumps leading to systems that are not low-cost [51,52]. We have developed a new approach based on open …”
Section: Novel Integrated Pre-concentrator Gas Sensor Microsystemmentioning
confidence: 99%
“…Research and development on microscale gas chromatographic (μGC) systems for analyzing mixtures of volatile organic compounds (VOCs) conducted over the past few decades has produced some significant advances in component device designs, system integration strategies, and performance [1][2][3]. Yet, early projections of inexpensive, pocket-sized instrumentation capable of autonomous, quantitative analysis of airborne VOC mixtures remain unrealized.…”
Section: Introductionmentioning
confidence: 99%